Is the Information Society a New Mode of Production? - Garnham, Nicholas (Javnost-The Public, 2004)
In analysing the current useful of a class analysis of the media this article places the political economy of the media in the context of a political economy of the Information Society. It argues that the Information Society does not refer to one thing or trend, but is made up of a number of competing, and often contradictory analyses of the development of the mode of production, each with different concepts of the role of information in economic development and different definitions of information workers. Media centric versions of the Information Society are then critiqued in the light of empirical evidence. Finally an assessment is made of what Information Society theory can contribute to our understanding of changes in the structure of the labour market associated with the growth of information work in relation to class and of globalisation through the concept of the death of distance.